2014
DOI: 10.1371/journal.pone.0091722
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Phylogenies Support Back-Migration from Beringia to Asia

Abstract: Recent arguments connecting Na-Dene languages of North America with Yeniseian languages of Siberia have been used to assert proof for the origin of Native Americans in central or western Asia. We apply phylogenetic methods to test support for this hypothesis against an alternative hypothesis that Yeniseian represents a back-migration to Asia from a Beringian ancestral population. We coded a linguistic dataset of typological features and used neighbor-joining network algorithms and Bayesian model comparison bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…25 A recent analysis of the Na-Den e and Yeniseian languages indicates a backmigration from Beringia into Siberia and central Asia rather than the reverse. 102 These events may not have any archeological correlates, underscoring the earlier observation that migrations take many forms. The later movements into and out of Beringia may represent phenomena of a very different order from the earlier movements of people into and out of Beringia.…”
Section: Post-lgm Beringia and Human Settlement Of The Americasmentioning
confidence: 96%
See 1 more Smart Citation
“…25 A recent analysis of the Na-Den e and Yeniseian languages indicates a backmigration from Beringia into Siberia and central Asia rather than the reverse. 102 These events may not have any archeological correlates, underscoring the earlier observation that migrations take many forms. The later movements into and out of Beringia may represent phenomena of a very different order from the earlier movements of people into and out of Beringia.…”
Section: Post-lgm Beringia and Human Settlement Of The Americasmentioning
confidence: 96%
“…Two mtDNA subclades in Northeast Asia that appear to have originated in Beringia are C1a and A2a; the movement of the latter into western and southern Siberia is thought to have taken place a few thousand years ago . A recent analysis of the Na‐Dené and Yeniseian languages indicates a back‐migration from Beringia into Siberia and central Asia rather than the reverse . These events may not have any archeological correlates, underscoring the earlier observation that migrations take many forms.…”
Section: Post‐lgm Beringia and Human Settlement Of The Americasmentioning
confidence: 97%
“…Researchers examined languages from Siberia, Alaska, and northern North America, looking for structural traits, such as the presence of plural pronouns. Using these traits to build an evolutionary-tree-like diagram, they found that the Siberian languages evolved alongside the Native American languages (11). This finding supports "at least a period of occupation and diversification within the Beringian area, and probably somewhere within the southwestern Alaskan area," says study coauthor Gary Holton of the University of Hawai'i at Manoa.…”
Section: Mounting Evidencementioning
confidence: 89%
“…In linguistics, the number of studies using computational phylogeny has recently increased (e.g. Gray & Atkinson 2003;Nakhleh et al 2005;Gray et al 2009;Prokić and Nerbonne 2008;Sicoli and Holton 2014;Bakker et al 2011;. Computational phylogenetic techniques have been used mainly for evolutionary studies of language families, and dialect and language classification in historical linguistics.…”
Section: Phylogenetic Approachmentioning
confidence: 99%